Coprecipitation technique to prepare ZnM2O6 powders - Deshpande, V. V.; Patil, M. M.; Navale, S. C.; Ravi, V. (Bulletin of Materials Science, 2005)
A simple coprecipitation technique was successfully applied for the preparation of pure ultrafine single phase, ZnNb2O6 (ZN). Ammonium hydroxide was used to precipitate Zn2+ and Nb5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees, produced ZN powders. For comparison, ZN powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Optimization and scale up of production of alkaline protease from Conidiobolus coronatus - Laxman, Ryali Seeta; Sonawane, A. P.; More, Shivaji V.; Rao, B. S.; Rele, M. V.; Jogdand, Vitthal V.; Deshpande, V. V.; Rao, M. B. (Process Biochemistry, 2005)
Alkaline protease secreted by Conidiobolus coronatus has been evaluated extensively in tanneries and finds application in pre-tanning operations in leather manufacture. It is important to produce the enzyme in inexpensive and optimized media on large scale for the process to be commercially viable. The present paper describes optimization of fermentation conditions in shake flasks and scale up of production to 100 L in fermentors. The production is complete in 2-3 days comparable to bacterial fermentations. The organism utilized several carbon sources such as starch, sucrose, lactose, glucose and fructose for production. Soyabean meal at an optimum concentration of 2-3% was found to be best inducer. Diammonium hydrogen phosphate, casamino acids and Hi-media peptone gave activities comparable to yeast extract. Preservation and stabilization studies showed that glycerol conferred considerable stabilization at room temperature while ammonium sulphate precipitated enzyme at 0.9 saturation was best with stability up to 2 years even at room temperature. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Conidiobolus; Fermentation; Optimization; scale up

Synthesis of bismuth oxide nanoparticles at 100 degrees C - Patil, M. M.; Deshpande, V. V.; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of ultrafine Bi2O3 particles at 80-100 degrees C under refluxing conditions. Freshly prepared bismuth hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 6-12 h. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. The thermal decomposition of bismuth hydroxide yields Bi2O3 only at 400 degrees C. This shows the advantage of the present method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these oven-dried powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of rutile from ATO and stearic acid - Patil, M. M.; Deshpande, V. V.; Deshpande, S. B.; Samuel, V.; Ravi, V. (Materials Letters, 2005)
Nanocrystalline titanium dioxide in the rutile phase has been obtained from the solid state reaction between ammonium titanyl oxalate (ATO) and stearic acid at 400 degrees C in air. The fine powders of ATO and stearic acid are mixed well using acetone in an agate mortar and pestle for 2 h. This mixture (weight ratio of ATO to stearic acid > 5) on heating at 400 degrees C produces rutile powders. For the ratios of ATO to stearic acid < 5, a mixture of anatase and rutile phases is obtained. Pure ATO yields anatase phase on decomposition at 400 degrees C. These powders were characterized by X-ray diffraction (XRD), BET surface area measurements and transmission electron microscopy (TEM) studies. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray techniques

Dielectric properties of BaTiO3 ceramics prepared from powders with bimodal distribution - Deshpande, S. B.; Potdar, H. S.; Patil, M. M.; Deshpande, V. V.; Khollam, Y. B. (Journal of Industrial and Engineering Chemistry, 2006)
BaTiO3 (BT) powders having bimodal distribution were synthesized successfully through a simple classical solid-state reaction route using cheap BaCO3 and TiO2 as starting materials. These powders were further processed in the form of green pellets to obtain dense BT ceramics having densities of similar to 94 similar to 96 % after sintering in air at 1350 and 1400 degrees C/4 h in air. The room temperature dielectric constant (epsilon(RT)) of similar to 1500 at 1 KHz frequency was increased to : 10000 at a Curie temperature (T-C) similar to 126 degrees C, showing a very sharp transition from a polar tetragonal to a non-polar cubic structure. The dielectric loss factor (tan 6) was similar to 1.5 %. SEM studies revealed the presence of dense microstructures having a distribution of smaller grains (size: 2 similar to 3 gm) surrounded by larger grains (>= 35 mu m). The ferroelectric hysteresis loop measurements on these samples gave values of spontaneous polarization (P-s) of similar to 12.0 mu C/cm(2), a coercive field (E-C) of similar to 2 similar to 2.5 kV/cm, and a dielectric strength (E-b) of similar to 48.0 kV/cm. DC-resistivity as high as 1.5 x 10(9) Omega-cm was obtained in these samples. All these results are quite comparable with reported ferroelectric/dielectric data and are discussed elaborately in this paper.
Keywords: BaTiO3; dielectric-ferroelectric properties; Microstructure; Sintering; stoichiometry